An Appraisal of Geo-Hydrological Control on the Occurrence of Prawn Broods along the Tidal Water courses of Indian Sunderbans - Das, Gautam Kumar (Indian Science Cruiser, 2004)
The present paper deals with the geo-hydrological control on the density of occurrence of penaeid prawn broods and the related fishing methods practised along the saltwater courses of the deltaic Sunderbans, Northeast India. The paper also elaborates the hazards associated with rampant fishing to cause river bank erosion and impediment in nutrient recycling in the ambient waters. The mangrove belts of Sunderbans which act as the chief source of nutrient supply to those water bodies also get badly affected by artificial means of fishing in addition to natural hazards arising from meteoric storms and cyclones. The author has tried to identify and delineate the geomorphic situations and other physicochemical environments that control the prolific occurrence of the post larvae of prawns which are later used for culture in brackish water coastal fisheries. Certain management measures have been proposed to safeguard the disaster following approaches related to morphological and hydrodynamic appraisement.